Ալիֆի և համզայի գործառույթները գրական արաբերենի ձևահնչյունային համակարգում՝ ըստ ալ-Խալիլ իբն Ահմադի «Քիթաբ ալ-Այն» աշխատության - Հ. Վ. Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Согласно арабской грамматической традиции, минимальные сегменты фонологической и морфологической (словообразовательной) структуры арабского языка называются харфами - единицами, представляющими собой сочетание согласного и гласного. Традиционно принято выделять 28 таких харфов. According to the Arabic linguistic tradition, harfs are minimal segments of phonological and morphological (derivational) structure of Arabic, which are combinations of consonants and vowels. Traditionally, 28 harfs like those are accepted.
Keywords: Philology; Linguistics; Language and Literature